Heat-sealing cover tape with multi-layer structure and preparation method of heat-sealing cover tape

By modifying the base layer of the cover tape and using a combination of polyurethane material and ultrafine tourmaline powder, a heat sealed cover tape with high strength and continuous anti-static function was prepared, solving the damage to electronic components by high-temperature sealing and The problem of unstable antistatic properties achieves effective bonding and stable antistatic effects at lower temperatures.

CN119410286APending Publication Date: 2025-02-11GUIXI RUOBANG ELECTRONICS SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411573559.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing heat sealing tapes are prone to damage to electronic components when used at high temperatures, and their antistatic properties are unstable and will weaken over time.

Method used

By modifying and optimizing the base layer of the cover tape, a high-strength base layer was prepared, and a polyurethane material with good thermal processing plasticity was used as the base material of the adhesive, combined with the coupling modified and activated ultrafine stone Powder, an adhesive layer with continuous anti-static function and good flow performance was prepared, and finally a heat sealing tape was formed by lamination technology.

Benefits of technology

It achieves a good adhesion effect at lower temperatures, reduces the damage to electronic components by high-temperature sealing, and makes the antistatic properties of the cover tape more stable and long-lasting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a heat-sealing cover tape with a multi-layer structure and a preparation method of the heat-sealing cover tape, and belongs to the technical field of preparation of layered products for packaging electronic components. The preparation method comprises the following step: processing the high-strength base material layer and the bonding layer with the anti-static function under the lamination pressure of 1-1.5 MPa. The base material layer of the cover tape is subjected to composite modification to obtain a high-strength base material layer with good flexibility and wear resistance, then a polyurethane material with good hot working plasticity is used as an adhesive base material, and tourmaline powder subjected to coupling modification and activation is utilized to prepare the cover tape. The bonding layer with a continuous anti-static function and good flowing performance is prepared, finally, the high-strength base material layer and the bonding layer with the anti-static function form the heat-sealing cover tape through a laminating technology, and the heat-sealing cover tape has good low-temperature heat-sealing and anti-static functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of layered products for electronic component packaging, and in particular relates to a multi-layer heat-sealing cover tape and a preparation method thereof. Background Art

[0002] Cover tape is usually called "cover film" or "package cover tape". It is an important material used to protect components during the packaging process of electronic components. It is generally made of plastic, metal or other composite materials, and is mainly used to cover and protect electronic components such as chips, sensors and discrete components. Cover tape is mainly used in the electronic component mounting industry. According to the shape of the carrier tape, it can be designed into an H-shaped cover tape. It is used with the carrier tape to carry and store electronic components such as resistors, capacitors, transistors, diodes, etc. in the pockets of the carrier tape. The cover tape is sealed above the pocket formed by the carrier tape to form a closed package to protect the electronic components from contamination and damage during transportation. In order to increase the adhesion between the cover tape and the carrier tape, glue can also be applied to the carrier tape by interval glue coating to increase the effective combination of the cover tape and the carrier tape. When the electronic components are mounted, the cover tape is peeled off, and the automatic mounting equipment takes out the components in the pocket one by one through the precise positioning of the index hole of the carrier tape, and mounts them on the integrated circuit board.

[0003] The cover tape is usually divided into two types: pressure-sensitive sealing and heat-sensitive sealing. Pressure-sensitive sealing refers to applying continuous pressure through the pressure roller of the sealing machine so that the pressure-sensitive adhesive on the cover tape adheres to the carrier tape to achieve the wrapping of electronic components. However, this method has high requirements on the pressure resistance of the carrier tape material. If the pressure resistance is low, it is easy to cause the carrier tape to be squeezed and crushed during pressure-sensitive sealing, thereby damaging the electronic components. Heat-sensitive sealing is a more commonly used technical method at present. It uses a sealing machine to apply a certain temperature and pressure to melt the hot melt adhesive of the cover tape and press it on the sealing surface of the carrier tape to achieve sealing. The advantage of this method is that the heat-sensitive tape used for heat-sensitive sealing is not sticky at room temperature and only has stickiness when heated. In addition, the sealing pressure required is small and will not cause damage to the carrier tape. When the cover tape is peeled off, it is easy to accumulate charges due to friction, thereby generating static electricity. These static electricity easily lead to the adsorption of dust and damage to electronic components. Therefore, it is of great value to involve a cover tape with anti-static function.

[0004] Patent CN115027115A discloses an environmentally friendly composite cover tape and its preparation process. The invention designs a composite cover tape having a PET layer, a PE layer and a TPE layer, and then composites the raw materials used for the PE layer and the TPE layer, and controls the weight ratio of the ethylene / sodium methacrylate copolymer in the TPE layer raw material, thereby achieving antistatic performance.

[0005] Patent CN103043302A discloses an environmentally friendly composite cover tape and its preparation process. The invention achieves antistatic performance by arranging a first antistatic layer under the substrate film layer. The first antistatic layer is obtained by coating a solution of one or a mixture of metal oxides, conductive carbon black, carbon nanotubes, organic conductive agents and ionic liquids.

[0006] Although the above two patents realize the antistatic function of the cover tape, due to the limitation of its own antistatic principle, the antistatic performance of each individual is quite different, and the antistatic performance will weaken over time. At the same time, the heat sealing temperature is mostly above 100°C. In this temperature range, if the heat cannot be dissipated to the environment in time, it is easy to have a "fatal effect" on the electronic components, causing the electronic components to be damaged and unusable.

[0007] Therefore, it is of great significance to develop a device with continuous and stable anti-static function while avoiding the adverse effects of excessively high heat sealing temperatures on electronic components. Summary of the invention

[0008] According to the shortcomings of the prior art, the present invention modifies and optimizes the base material layer of the cover tape to obtain a high-strength base material layer with good wrapping and flexibility, and then uses a polyurethane material with good thermal processing plasticity as the adhesive base material, and prepares an adhesive layer with continuous antistatic function and good flow performance by coupling modified and activated ultrafine tourmaline powder, and finally forms a heat-sealed cover tape by laminating the high-strength base material layer and the adhesive layer with antistatic function through lamination technology, thereby solving the technical problems raised in the background technology. Specifically, the technical solution of the present invention includes the following contents: A multi-layer heat-sealing cover tape, wherein the heat-sealing bag cover is composed of a high-strength base material layer and an adhesive layer with an antistatic function.

[0009] Furthermore, the method for preparing the high-strength substrate layer comprises the following steps: Poly(p-phenylene terephthalamide), polyester TPU and polyurethane resin are mixed in a weight ratio of 1:2 to 3:1 to obtain a mixture, the mixture is blended at a speed of 50 r / min to 100 r / min for 10 min to 15 min in a temperature environment of 170° C. to 190° C., and then poured into a mold and naturally cooled to form the high-strength substrate layer.

[0010] Furthermore, the weight ratio of the poly(p-phenylene terephthalamide), polyester TPU and polyurethane resin is 1:3:1.

[0011] Furthermore, the method for preparing the adhesive layer with antistatic function comprises the following steps: The tourmaline powder and the coupling agent are mixed to obtain a mixture, and then the mixture is dried by microwave heating to obtain activated tourmaline powder; The activated tourmaline powder, styrene-butadiene latex and mixed emulsifier are stirred to obtain a mixed solution, the mixed solution is stirred with azobisisobutyronitrile to obtain a reaction solution, the reaction solution is heated to 65° C. to 75° C. and reacted for 5 h to 6 h to obtain the adhesive layer with antistatic function.

[0012] Furthermore, the tourmaline powder is obtained by screening with a 1000-mesh sieve.

[0013] Furthermore, the coupling agent is a mixture of vinyltriethoxysilane and ethanol in a weight ratio of 1:3.

[0014] Furthermore, the weight ratio of the tourmaline powder to the coupling agent is 10-20:1.

[0015] Furthermore, the mixed emulsifier is a mixture of sodium lauryl sulfate and AEO-9 in a weight ratio of 1:1.

[0016] Furthermore, the weight ratio of the activated tourmaline powder, styrene-butadiene latex and mixed emulsifier is 1:30-40:0.05-0.1.

[0017] Furthermore, the amount of azobisisobutyronitrile added is 0.01 times the weight of the mixed solution.

[0018] A method for preparing a multi-layer heat-sealing cover tape, the method comprising the following steps: The high-strength base layer and the adhesive layer with antistatic function are obtained by laminating at a pressure of 1MPa~1.5MPa.

[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention firstly modifies and optimizes the base material layer of the cover tape, and uses poly(p-phenylene terephthalamide) with good wear resistance and tear resistance and polyester-type TPU and polyurethane resin with good flexibility, and obtains a high-strength base material layer with both wear resistance and flexibility through compounding and high-temperature blending. Then, the ultra-fine tourmaline powder is first modified and activated with organic silicon, and microwave heating is used to prevent the ultra-fine tourmaline powder from agglomerating, and then a coupling reaction is carried out with a coupling agent containing organic silicon, so that the surface thereof obtains carbon-carbon unsaturated double bonds that can be polymerized and combined with organic matter, and then the tourmaline powder is mixed with styrene-butadiene latex, and the mixed emulsifier can improve the dispersibility of the activated tourmaline powder in styrene-butadiene latex, and finally azobisisobutyronitrile is added, and a heating reaction is carried out, so that the tourmaline powder is evenly dispersed in the adhesive layer, and the anti-static modification is achieved. The butadiene-styrene structure contained in the butadiene latex is easy to produce flexible structures such as carbon chains with longer and larger degrees of freedom and saturated carbon ring structures with good degrees of freedom during the polymerization process with tourmaline powder, which can easily allow the polymer to bend and rotate freely, thereby making the finally prepared adhesive layer with antistatic function have good flow properties. The adhesive layer with antistatic function with good flowability can achieve good adhesion at a lower temperature, reducing the adverse effects of heat sealing at too high a temperature on damage to electronic components, and making the antistatic performance of the cover tape more stable and durable. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below through the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available or can be prepared by known methods.

[0022] Poly(p-phenylene terephthalamide) was purchased from Suzhou Hengsi'an Protection Technology Co., Ltd.; Polyester TPU is purchased from Zhejiang Huafeng Thermoplastic Polyurethane Co., Ltd.; Polyurethane resin was purchased from Zhejiang Huafeng Synthetic Resin Co., Ltd.; Styrene butadiene latex was purchased from Zhejiang Tianchen Rubber Industry Co., Ltd.

[0023] Preparation Example 1: The method for preparing a high-strength substrate layer specifically includes the following steps: 1 part by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 1 part by weight of polyurethane resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 170°C, and the mixture was blended at a speed of 50 r / min for 10 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0024] Preparation Example 2: The method for preparing a high-strength substrate layer specifically includes the following steps: 1 part by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 1 part by weight of polyurethane resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 180°C, and the mixture was blended at a speed of 50 r / min for 12 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0025] Preparation Example 3: The method for preparing a high-strength substrate layer specifically includes the following steps: 1 part by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 1 part by weight of polyurethane resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 180°C, and the mixture was blended at a speed of 100 r / min for 13 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0026] Preparation Example 4: The method for preparing a high-strength substrate layer specifically includes the following steps: 1 part by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 1 part by weight of polyurethane resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 190°C, and the mixture was blended at a speed of 100 r / min for 15 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0027] Preparation Example 5: The method for preparing a high-strength substrate layer specifically includes the following steps: 1 part by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 1 part by weight of polyurethane resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 190°C, and the mixture was blended at a speed of 150 r / min for 15 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0028] Preparation Example 6: The method for preparing a high-strength substrate layer specifically includes the following steps: 2 parts by weight of poly(p-phenylene terephthalamide), 3 parts by weight of polyester TPU and 2 parts by weight of HY604-850 solid epoxy resin were placed in a vacuum drying oven and dried at 70°C for 10 hours. Then they were placed in an extruder, the extruder was heated to 200°C, and the mixture was blended at a speed of 100 r / min for 15 minutes. After the blending was completed, the obtained blend was poured into a flat mold and cooled naturally to form a high-strength substrate layer.

[0029] The high-strength substrate layers obtained in Preparation Examples 1 to 6 were tested for impact performance and bending performance according to "GB / T 2571-1995 Impact Test Method for Resin Castings" and "GB / T 2570-1995 Bending Performance Test Method for Resin Castings", and the deformation was observed. The results are shown in the following table: in conclusion: (1) It can be seen from the data in the above table that under certain preparation conditions, Preparation Examples 1 to 4 exhibit good bending toughness and impact strength. This property helps to reduce the adverse effects of damage to electronic components caused by deformation of the cover tape when subjected to external forces.

[0030] (2) In Preparation Example 5, due to the excessively fast rotation speed, the bending strength of the high-strength substrate layer is increased, but the impact resistance is reduced. When impacted, the substrate is easily deformed, causing damage to the electronic components.

[0031] (3) In Preparation Example 6, due to the high temperature, the impact strength of the high-strength substrate layer is increased, but due to the low bending strength, the material is prone to breakage when stretched or compressed, causing damage to the electronic components.

[0032] Preparation Example 8: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 10:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0033] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 30 weight parts of styrene-butadiene latex and 0.05 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0034] Azobisisobutyronitrile (0.01 times the weight of the mixed solution) was mixed with the mixed solution and stirred, and then heated to 65°C for 5 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0035] Preparation Example 9: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 10:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0036] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 32 weight parts of styrene-butadiene latex and 0.06 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0037] 0.01 times the weight of the mixed solution of azobisisobutyronitrile was mixed with the mixed solution and stirred, and then heated to 75°C for 6 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0038] Preparation Example 10: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 20:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0039] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 34 weight parts of styrene-butadiene latex and 0.07 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0040] 0.01 times the weight of the mixed solution of azobisisobutyronitrile was mixed with the mixed solution and stirred, and then heated to 75°C for 6 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0041] Preparation Example 11: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 10:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0042] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 36 weight parts of styrene-butadiene latex and 0.08 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0043] Azobisisobutyronitrile (0.01 times the weight of the mixed solution) was added to the mixed solution and stirred, and then heated to 75°C for 6 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0044] Preparation Example 12: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 10:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0045] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 38 weight parts of styrene-butadiene latex and 0.09 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0046] 0.01 times the weight of the mixed solution of azobisisobutyronitrile was added to the mixed solution and stirred, and then heated to 65°C for 5 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0047] Preparation Example 13: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: Vinyl triethoxysilane and ethanol were placed in a beaker at a weight ratio of 1:3 and stirred to form a coupling agent. Then, 1000-mesh tourmaline powder and the coupling agent were mixed at a weight ratio of 10:1 and placed in a heating plate and stirred. The mixture was then placed in a microwave muffle furnace and heated to 40°C for 15 hours. After the reaction was completed, the mixture was allowed to cool to room temperature to obtain activated tourmaline powder.

[0048] Sodium lauryl sulfate and AEO-9 were put into a beaker in a weight ratio of 1:1 and stirred to form a mixed emulsifier. 1 weight part of activated tourmaline powder, 40 weight parts of styrene-butadiene latex and 0.1 weight part of the mixed emulsifier were stirred to obtain a mixed solution.

[0049] Azobisisobutyronitrile (0.01 times the weight of the mixed solution) was added to the mixed solution and stirred, and then heated to 75°C for 6 hours. After the reaction, the solution was poured into ice ethanol and allowed to settle, and then filtered and separated and naturally dried to obtain an adhesive layer with antistatic function.

[0050] Preparation Example 14: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: The 1000-mesh tourmaline powder in Preparation Example 12 was replaced with 500-mesh tourmaline powder, and the other conditions remained the same as in Preparation Example 12.

[0051] Preparation Example 15: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: The tourmaline powder in Preparation Example 12 was replaced with conductive graphene powder, and the other conditions remained the same as in Preparation Example 12.

[0052] Preparation Example 16: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: The heating reaction in the microwave muffle furnace in Preparation Example 12 was replaced by a room temperature reaction, and the other conditions remained the same as in Preparation Example 12.

[0053] Preparation Example 17: The method for preparing an adhesive layer with antistatic function specifically comprises the following steps: The styrene-butadiene latex in Preparation Example 12 was replaced with polystyrene emulsion, and the other conditions were kept consistent with Preparation Example 13.

[0054] Embodiment 1: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 1 and the adhesive layer with antistatic function obtained in Preparation Example 8 were respectively controlled to have a thickness of 20 μm and 10 μm using a scraper coater, and then the 20 μm thick high-strength substrate layer and the 10 μm thick adhesive layer with antistatic function were obtained by lamination pressure processing at 1 MPa.

[0055] Embodiment 2: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 2 and the adhesive layer with antistatic function obtained in Preparation Example 9 were respectively controlled to have a thickness of 22 μm and 12 μm using a scraper coater, and then the high-strength substrate layer with a thickness of 22 μm and the adhesive layer with an antistatic function with a thickness of 12 μm were obtained by lamination pressure processing at 1 MPa.

[0056] Embodiment 3: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 3 and the adhesive layer with antistatic function obtained in Preparation Example 10 were respectively controlled to have a thickness of 24 μm and 14 μm using a scraper coater, and then the high-strength substrate layer with a thickness of 24 μm and the adhesive layer with an antistatic function with a thickness of 14 μm were obtained by lamination pressure processing at 1.5 MPa.

[0057] Embodiment 4: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 4 and the adhesive layer with antistatic function obtained in Preparation Example 11 were respectively controlled to have a thickness of 26 μm and 16 μm using a scraper coater, and then the high-strength substrate layer with a thickness of 26 μm and the adhesive layer with an antistatic function with a thickness of 16 μm were obtained by lamination pressure processing at 1.5 MPa.

[0058] Embodiment 5: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 4 and the adhesive layer with antistatic function obtained in Preparation Example 12 were respectively controlled to have a thickness of 28 μm and 18 μm using a scraper coater, and then the high-strength substrate layer with a thickness of 28 μm and the adhesive layer with an antistatic function with a thickness of 18 μm were obtained by lamination pressure processing at 2 MPa.

[0059] Embodiment 6: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The high-strength substrate layer obtained in Preparation Example 4 and the adhesive layer with antistatic function obtained in Preparation Example 13 were respectively controlled to have a thickness of 28 μm and 20 μm using a scraper coater, and then the high-strength substrate layer with a thickness of 28 μm and the adhesive layer with an antistatic function with a thickness of 20 μm were obtained by lamination pressure processing at 2 MPa.

[0060] Comparative Example 1: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The adhesive layer with antistatic function in Example 6 was replaced by the adhesive layer with antistatic function obtained in Preparation Example 14, and the other conditions remained the same as in Example 6.

[0061] Comparative Example 2: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The adhesive layer with antistatic function in Example 6 was replaced by the adhesive layer with antistatic function obtained in Preparation Example 15, and the other conditions remained the same as in Example 6.

[0062] Comparative Example 3: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The adhesive layer with antistatic function in Example 6 was replaced by the adhesive layer with antistatic function obtained in Preparation Example 16, and the other conditions remained the same as in Example 6.

[0063] Comparative Example 4: A method for preparing a multi-layer heat-sealing cover tape specifically comprises the following steps: The adhesive layer with antistatic function in Example 6 was replaced by the adhesive layer with antistatic function obtained in Preparation Example 17, and the other conditions remained the same as in Example 6.

[0064] Comparative Example 5: The thickness of the high-strength substrate layer and the adhesive layer with antistatic function in Example 6 were increased to 30 μm and 22 μm respectively, and the other conditions remained the same as in Example 6.

[0065] The surface resistance values ​​of the multi-layer heat-sealed cover tapes obtained in Examples 1 to 6 and Comparative Examples 1 to 5 were measured using an AS982 surface resistance tester. Heat sealing was then performed at 60° C. and the peel strength was measured. The results are shown in the following table: From the data in the above table, we can see that: (1) The multilayer heat-sealing cover tapes of Examples 1 to 6 have a lower surface resistance, and the surface resistance changes little after long-term storage. Moreover, heat sealing can be achieved at a relatively low temperature of 60°C, which reduces the adverse effects of high-temperature sealing on damage to electronic components. The peel strength after sealing is good, indicating that the heat sealing effect can be achieved.

[0066] (2) It can be seen from Comparative Example 1 that although it has a certain antistatic effect, the larger particle size of the tourmaline powder affects the degree of polymerization between it and the styrene-butadiene latex, resulting in an unstable distribution of the tourmaline powder in the adhesive layer. It is easy to agglomerate when stored for a long time, so the antistatic effect is not long-lasting.

[0067] (3) It can be seen from Comparative Example 2 that although the conductive graphene powder has good conductive properties, the degree of polymerization with styrene-butadiene latex is not high, and it is easy to agglomerate, resulting in uneven distribution of the conductive graphene and difficulty in forming a continuous and uniform conductive path. In addition, as the storage time increases, the degree of agglomeration also increases, so the antistatic effect is poor. At the same time, the conductive graphene powder will also affect the flow properties of the adhesive layer and increase the difficulty of heat sealing.

[0068] (4) It can be seen from Comparative Example 3 that since the particle size of 1000 mesh tourmaline powder is small, it is easy to agglomerate, resulting in uneven distribution of tourmaline powder. Therefore, the cross-linking effect between tourmaline powder and coupling agent is poor under low room temperature environment, which will affect the antistatic effect of the multi-layer structure heat-sealing cover tape.

[0069] (5) It can be seen from Comparative Example 4 that polystyrene emulsion is not easy to polymerize with tourmaline powder to form a uniform adhesive layer, and the strength of polystyrene itself is relatively low, which causes the cover tape to be easily damaged and fall off.

[0070] (6) It can be seen from Comparative Example 5 that a cover tape that is too thick may require a higher temperature to achieve heat sealing, and high temperature is not conducive to the protection of electronic components.

[0071] The above-described embodiments provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected.

Claims

1. A multi-layer heat-sealing cover tape, characterized in that: The heat-sealed bag cover consists of a high-strength base material layer and an adhesive layer with an antistatic function.

2. The multi-layer heat-sealing cover tape according to claim 1, characterized in that: The method for preparing the high-strength substrate layer comprises the following steps: Poly(p-phenylene terephthalamide), polyester TPU and polyurethane resin are mixed to obtain a mixture, the mixture is blended at a speed of 50 r / min to 100 r / min for 10 min to 15 min in a temperature environment of 170° C. to 190° C., and then poured into a mold and naturally cooled to form the high-strength substrate layer.

3. The multi-layer heat-sealing cover tape according to claim 2, characterized in that: The weight ratio of the poly(p-phenylene terephthalamide), polyester TPU and polyurethane resin is 1:3:

1.

4. The multi-layer heat-sealing cover tape according to claim 1, characterized in that: The method for preparing the adhesive layer with antistatic function comprises the following steps: mixing tourmaline powder and a coupling agent to obtain a mixture, and then heating the mixture by microwave to obtain activated tourmaline powder; The activated tourmaline powder, styrene-butadiene latex and mixed emulsifier are stirred to obtain a mixed solution, the mixed solution is stirred with azobisisobutyronitrile to obtain a reaction solution, the reaction solution is heated to 65° C. to 75° C. and reacted for 5 h to 6 h to obtain the adhesive layer with antistatic function.

5. The multi-layer heat-sealing cover tape according to claim 4, characterized in that: The coupling agent is a mixture of vinyl triethoxysilane and ethanol in a weight ratio of 1:

3.

6. The multi-layer heat-sealing cover tape according to claim 4, characterized in that: The weight ratio of the tourmaline powder to the coupling agent is 10-20:

1.

7. The multi-layer heat-sealing cover tape according to claim 4, characterized in that: The mixed emulsifier is a mixture of sodium lauryl sulfate and AEO-9 in a weight ratio of 1:

1.

8. The multi-layer heat-sealing cover tape according to claim 4, characterized in that: The weight ratio of the activated tourmaline powder, styrene-butadiene latex and mixed emulsifier is 1:30-40:0.05-0.

1.

9. The multi-layer heat-sealing cover tape according to claim 4, characterized in that: The amount of azobisisobutyronitrile added is 0.01 times the weight of the mixed solution.

10. A method for preparing a multi-layer heat-sealing cover tape as claimed in any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: The high-strength base layer and the adhesive layer with antistatic function are processed by lamination pressure of 1MPa~2MPa.

Citation Information

Patent Citations

  • Cover tape

    CN103043302A